Isolasi dan Karakterisasi Bakteri Actinomycetes Pada Rhizosfer Tanaman Jagung (Zea Mays) di Provinsi Gorontalo - Anwar, Susilo (Universitas Bojonegoro, 2025)
Actinomycetes are gram-positive bacteria that play an important role in soil health and plant growth, and have the potential as biocontrol agents. Actinomycetes are a group of bacteria that are widely distributed in nature, including in the sea, soil, litter, water, and in extreme environments. The diversity of Actinomycetes species is greatly influenced by the physicochemical factors of the surrounding environment. This study aims to identify Actinomycetes bacteria found in the rhizosphere of corn plants (Zea mays L.) in the Gorontalo region. The research method includes descriptive with a qualitative and quantitative approach, using purposive sampling technique for soil sample collection. This was conducted at three locations on the corn hills in Mohiyolo Village, Asparaga District, Gorontalo Regency. followed by the isolation and culture of Actinomycetes bacteria using selective media. Identification was carried out based on colony morphology and microscopic characterization of the successfully isolated bacteria. Identification was carried out using the Gram staining method and morphological analysis. The research results show the presence of Actinomycetes species with diverse morphological characteristics and microscopic characterization, revealing that most of the obtained isolates are gram-positive bacteria with coccus and bacillus shapes.